Birinapant sensitizes platinum-resistant carcinomas with high levels of cIAP to carboplatin therapy - V. La (Nature Portfolio, 2017)
Combination therapy: sensitizing platinum-resistant tumors Carboplatin efficacy can be restored by administering it with birinapant, a drug combination that targets platinum-resistant cancer cells. Platinum-based chemotherapeutics are used to treat almost 50% of cancer patients. Despite excellent initial response rates, tumor growth recurs in most patients as they develop resistance to therapy. Sanaz Memarzadeh and colleagues at the University of California, Los Angeles, show that the addition of birinapant to carboplatin eliminates platinum-resistant ovarian cancer cells by degrading the cell death-inhibiting proteins cIAP1 and cIAP2. Carboplatin and birinapant co-therapy restored the efficacy of the chemotherapeutic in human tumor samples and in mice with platinum-resistant tumors. Furthermore, the levels of cIAP protein in the resistant cells were predictive of the therapeutic response. These findings will help to select clinical trial patients that are most likely to benefit from this combination therapy.